Shear strengthening of concrete deep beams using pre-fabricated strain-hardening cementitious composite plates. (1st March 2023) - Khalil, Abd El-Hakim A.; Atta, Ahmed M.; Baraghith, Ahmed T.; Behiry, Reda N.; Soliman, Osama E.
Highlights: P-SHCC plates were investigated for shear strengthening of RC deep beams. The effect of net spacing, width, embedded steel reinforcement ratio and the prestressing level were examined. Twelve RC deep beams under four-point loading have been experimentally tested. A shear capacity increase of 6.9–68.5% was achieved. Two analytical models were proposed using strut-and-tie model and regression analysis for predicting the ultimate shear capacity of the strengthened DBs. Abstract: This study investigates the efficiency of near surface embedded (NSE) pre-fabricated strain-hardening cementitious composite (P-SHCC) plates for shear strengthening of reinforced concrete deep beams (RC-DBs) through testing 12 identical specimens. For this purpose, P-SHCC plates of 20 mm thickness have been prepared according to the test variables, cured for about 30 days, and then dipped into the concrete cover of the strengthened DBs at the critical shear span. The use of pre-fabricated plates is intended to alleviate any volumetric change issues associated with SHCC material. The studied parameters were the net spacing between the P-SHCC plates (0, 75, 112, and 150 mm), the width of the strengthening plates (60, 75, and 90 mm), and the ratio of steel reinforcement embedded inside the P-SHCC plates (0 %, 0.67 %, 1.50 %, and 3.00 %). Furthermore, the prestressing level relative to the yielding strain of the steel reinforcement embedded inside the P-SHCC plates was of interest. Experimental results exhibited a successful employment of the P-SHCC plates in enhancing the ultimate load capacity of RC deep beams, especially when prestressing was introduced. The gain in the ultimate capacity reached up to 68.5 %, relative to the un-strengthened control beam (BC), depending on the test parameters. Besides, incorporating steel reinforcement inside the P-SHCC plates had a pronounced effect on both the serviceability and ductility characteristics of the strengthened DBs. Specimens strengthened by reinforced P-SHCC plates demonstrated around 1.57-times improvement in energy absorption capacity when compared to their counterparts strengthened by plain P-SHCC plates. Finally, a strut-and-tie model (STM) in addition to a simpler equation based on regression analysis were used to assess the shear capacity of the strengthened DBs, considering the contribution of P-SHCC plates. The proposed two equations were in good accord with the experimental results.